Improving Students' Participation in the English Class by Implementing ICTS (2018)
ABSTRACT: This final report is the result of an action research project conducted in a public school in the municipality of Bello, Antioquia. The objective of this project was to provide students with new experiences applying different teaching strategies, implementing group work methodologies, and taking advantage of current and innovative ICT's resources sparsely applied at the institution, in order to impact positively students' participation and interaction in the classroom. The research ran by two academic semesters and it was conducted in the Institución Educativa Sagrado Corazón (IESC). To acquire data were applied methods such as observations, interviews and visual records. At the end of this paper, the findings of this proposal are reported.